The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13063-020-04679-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine plus personal protective equipment versus standard personal protective equipment alone for the prevention of COVID-19 infections among frontline healthcare workers: the HydrOxychloroquine Prophylaxis Evaluation(HOPE) trial: A structured summary of a study protocol for a randomized controlled trial

Abstract: Objectives: To evaluate the effect of the combination of hydroxychloroquine (HCQ) and standard personal protective equipment (PPE) compared to the use of standard personal protective equipment alone on the proportion of laboratory confirmed COVID-19 infections among frontline healthcare workers(HCWs) in India Trial design: HOPE is an investigator initiated multi-centre open-label parallel group randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In support of our contentions however other investigators from India assuming an attack rate of 10% and a modest but pragmatic and reasonable absolute risk reduction of 2.5% attest to needing a sample size of over 6000 participants to address the question of efficacy of HCQ as a prophylactic measure. 26 It is however surprising that the trialists here continue to adopt the dosing scheme of the ICMR which has no evidentiary basis whatsoever and is clearly considered to deliver suboptimal doses. Simulation from the University of Minnesota 27 used to drive the RCT reported in the New England Journal of Medicine from Minnesota 17 and other centres in North America is the only available pharmacologic basis to provide a trial prescription for appropriate testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our contentions however other investigators from India assuming an attack rate of 10% and a modest but pragmatic and reasonable absolute risk reduction of 2.5% attest to needing a sample size of over 6000 participants to address the question of efficacy of HCQ as a prophylactic measure. 26 It is however surprising that the trialists here continue to adopt the dosing scheme of the ICMR which has no evidentiary basis whatsoever and is clearly considered to deliver suboptimal doses. Simulation from the University of Minnesota 27 used to drive the RCT reported in the New England Journal of Medicine from Minnesota 17 and other centres in North America is the only available pharmacologic basis to provide a trial prescription for appropriate testing.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore logical to ask as to whether or not HCQ imparts protection beyond that offered by standard measures such as use of personal protective equipment (PPE). The overall design of the HOPE trial 26 is therefore compelling as it seeks to evaluate comparative efficacy of a standard protective measure such as use of personal protective equipment (PPE) alone measured against use of PPE with HCQ as an adjunct.…”
Section: Discussionmentioning
confidence: 99%
“…There are also multiple trials studying the role of hydroxychloroquine in the prophylaxis of COVID-19. 31 37 Two randomized controlled trials did not show any benefit to pre- or postexposure prophylaxis with hydroxychloroquine. 38 , 39 Thus, we do not recommend hydroxychloroquine or azithromycin for this purpose at this time.…”
Section: Questionsmentioning
confidence: 99%
“…These drugs have demonstrated to be effective in inhibiting the replication of SARS-CoV-2 in experimental models (figure 2) (Italian Medicine Agency) and have been increasingly tested for COVID-19 in many clinical studies. Specifically, many studies, which are currently ongoing, are evaluating the effects of hydroxychloroquine as prophylactic agent (Lother et al, 2020;Niriella et al, 2020;Tirupakuzhi Vijayaraghavan et al, 2020). At the moment, only one randomized, double-blind, placebo-controlled study on the prophylactic role of hydroxychloroquine was concluded.…”
Section: Clinical Evidence Of Immunomodulatory and Anti-inflammatory mentioning
confidence: 99%